Equal Respect, Equitable Treatment: Core Commitments for Responding to Diversity and Inequality in the Health System - Rink, Susan; Jiwani, Bashir; Adurogbangba, Mojisola (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
The Fraser Health Authority (FHA) has established a framework of commitments to guide a range of issues from incorporating diversity, equity, and inclusion in clinical and policy decisions and responding to the historical and continuing discrimination against First Nations, Métis, and Inuit peoples, to creating psychologically safe environments, and dealing with harassment, bullying and other disrespectful behaviours. FHA Ethics Services hosted a workshop as part of the 2023 Canadian Bioethics Society-Société canadienne de bioéthique (CBS-SCB) Workshop and Community Forum to create an opportunity for critical reflection and discuss strategic responses for the organization to live up to these commitments. This paper summarizes the workshop and identifies key insights and issues that emerged as areas that should be addressed in responding to diversity and inequality in the health system.